A guide to taming a toxin: recombinant immunotoxins constructed from Pseudomonas exotoxin A for the treatment of cancer - Weldon, John E. (2011)
PSEUDOMONAS: exotoxin A (PE) is a highly toxic protein secreted by the opportunistic pathogen Pseudomonas aeruginosa. The modular structure and corresponding mechanism of action of PE make it amenable to extensive modifications that can redirect its potent cytotoxicity from disease to a therapeutic function. In combination with a variety of artificial targeting elements, such as receptor ligands and antibody fragments, PE becomes a selective agent for the elimination of specific cell populations. This review summarizes our current understanding of PE, its intoxication pathway, and ongoing efforts to convert this toxin into a treatment for cancer.